Deep Learning Approach Through Meaningful, Mindful, and Joyful Learning: A Library Research - Feriyanto, F; Anjariyah, Deka (Electronic Journal of Education, Social Economics and Technology, 2024)
In modern education, fostering effective learning strategies is essential to improve educational outcomes. This study explores the integration of Meaningful Learning, Mindful Learning, and Joyful Learning within the Deep Learning approach, aiming to enhance student engagement and comprehension. Meaningful Learning connects new knowledge with prior understanding, Mindful Learning emphasizes full attention and reflection, and Joyful Learning creates an enjoyable and motivating environment. Using a library research method, this study analyzed data from journal articles, books, and prior studies published between 2000 and 2024 to examine how these approaches support Deep Learning implementation. Results indicate that Meaningful Learning facilitates critical thinking and problem-solving skills through project-based and gamified educational methods. Mindful Learning enhances cognitive abilities, focus, and academic performance using techniques such as mindfulness training and AI-assisted personalization. Joyful Learning fosters emotional engagement and retention through arts integration, game-based activities, and scaffolded learning. Together, these approaches improve conceptual understanding, creativity, and motivation. The study concludes that integrating these three approaches within Deep Learning provides a holistic framework for enhancing educational quality. Future research should investigate the application of this framework across diverse educational settings, including technology-driven and distance learning environments, to maximize its effectiveness.